Mie-Nyam (Tenggiri Fish Noodles) Business Strategy Spinach in Improving the Competitiveness of Healthy Noodles Based on Processed Fish with The Grand Strategy Matrix - Sumartini, Sumartini; Alvina, Zahriani; Defi, An Naim; Armadani, Novi (Jurnal Segara, 2024)
This study aims to analyze the business strategy of the innovative product "Mie-Nyam", namely spinach noodles with mackerel fish, in increasing competitiveness in the fishery-based healthy instant noodle industry. This product offers higher nutritional value than conventional instant noodles, with the addition of natural ingredients such as mackerel which is rich in protein and spinach leaves which are rich in nutrients. SWOT analysis and Grand Strategy Matrix are used to evaluate the strengths, weaknesses, opportunities, and threats faced by Mie-Nyam. New innovations in instant noodle products and packaging will raise new challenges regarding how the right marketing strategy and analysis are to determine whether or not a business is feasible, one of the analyses used is SWOT analysis using the grand strategy matrix. Based on the results of the analysis, MieNyam's position is in Quadrant II (Diversification) meaning that in this quadrant the business has strength but faces external threats. The strategy that must be implemented is to use strength to take advantage of long-term opportunities by means of a diversification strategy both in product variants and promotion and marketing diversification strategies.